Writing: Its Tools and Connotations The Invariable and the Varying: (Al Jahiz as an archetype) - ALabidi, Leila Y. (Al-Adab Journal, 2022)
The following article is concerned with writing as a human and existential reality that had insofar lured the interest of the ancient Arabs, mainly in the field of literature, for they examined, distinctively, the written verb in its transmission and acceptance, and through its relationship to traditional tools used in writing such as ink, paper and pen. Our reliance on an old Arabic archive did not prevent us from observing the transformations that had occurred in writing while shifting to the electronic stage, whatever its importance, there is no real disjointing between the classical and the new-fangled types of writing. Within this specific context, we mean by "writing" the original implication that the ancient Arabs called "in-ink" (a word derived from ink) and this without neglecting any of its seminal meanings in the connotation of the creative and structural writing, which finds its best idiomatic configuration in literature. And if we have been chiefly concerned with the Arab theory of writing through Al-Jahez in particular (while focusing on the symbolic implications of its tools in the Arabic/ Islamic imagination by disassembling, analyzing and interpreting), we have not the least bit failed to spot the tribulations which the contemporary Arabic writing is undergoing during the electronic globalization era. We are, thus, striving to understand as well as benefit as much as possible from modern anthropological knowledge.